DAMPAK DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP LANSIA - Ekasari, Mia Fatma; Hanggit Lestari, Puspita; Nurhasanah, Aan; Carolina Hapsari, Dina; Endah Pangastuti, Tri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Background: Decreased body function in the elderly results in a decrease in the quality of life, family support is one form of coping system, so this can help the elderly achieve their developmental tasks as an elderly person. The purpose of this study is to determine the relationship between family support and the quality of life of the elderly in RW 01 Kelurahan Lubang Buaya. Methods: This study uses quantitative methods with descriptive analytical design and coss-sectional approach. The study population was all elderly in RW 01 Kelurahan Lubang Buaya as many as 392 elderly and the sample taken was 71 elderly using simple random sampling technique. Data collection using questionnaires and data analysis techniques using Chi-Square test. Results: The results showed that there was a relationship between family support (p = 0.033) on the quality of life of the elderly, and there was no relationship between age (p = 0.064), gender (p = 0.210), and family living status (0.161) on quality live. Conclusion: There is a significant relationship between family support for the quality of life of the elderly in RW 01 Kelurahan Lubang Buaya